Comparing healthcare providers and primigravida women's attitudes towards normal vaginal delivery - Ronak Shahoee; Farzaneh Zaheri; Leyla Hashemi Nasab; Simin Nazarian; Fariba Ranaie (Kurdistan University of Medical Sciences, 2015)
Background and Aim: Pregnancy and delivery are among the most significant life events for women and their families. Currently, the rate of delivery by cesarean section has increased significantly due to women's lack of knowledge about and negative attitudes towards normal vaginal delivery. Moreover, the complications of cesarean section have turned motherhood into an unpleasant experience. The aim of this study was to compare healthcare providers and primigravida women's attitudes towards normal vaginal delivery. Methods: In total, 637 primigravida women and 154 healthcare professionals were recruited from Sanandaj city, Iran, to this descriptive-analytical study. The data collection instruments were a researcher-made demographic questionnaire and seventeen questions on attitude towards normal vaginal delivery. Questions were scored on a five-point Likert scale. The SPSS software as well as the Chi-square and the t tests were used for data analysis. Findings: The percentage of healthcare providers having a positive attitude towards normal vaginal delivery was significantly higher than primigravida women who did not have such an attitude (33.1% vs. 10% P value = 0.001). However, the percentage of primary health care providers (28.3%) and clinical care providers' (43.8%) who had positive attitudes towards normal vaginal delivery was not statistically significant from each other (P = 0.143). Conclusion: Lack of knowledge about the routes of delivery and the mechanism of normal vaginal delivery as well as lack of psychological support during delivery have increased women's tendency for having a delivery by cesarean section. Educational programs need to be implemented for enhancing women's knowledge about the benefits of normal vaginal delivery.